PENGARUH PERMAINAN HOP PINGPONG TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK AMALIA KECAMATAN MANDAH TEMBILAHAN - Ayu Andira; Yeni Solfiah; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract : This study aims to determine how much influence the hop ping pong game has on the ability to recognize the concept of numbers in children aged 4-5 years at Kindergarten Amalia, Mandah District. In this study using the experimental method with a one group pretest posttest design. The total population of children in Kindergarten Amalia, Mandah sub-district, is 15 children consisting of 7 boys and 8 girls. The data collection technique used in this study was to use an observation sheet on the ability to recognize the concept of numbers in early childhood. Data analysis technique using t-test. From the results of data analysis it can be concluded that there is a significant difference in the ability to recognize the concept of numbers before and after being given the hop pingpong game. Based on the results of the hypothesis testing obtained, there was an effect of the application of the pingpong hop game on the ability to recognize the concept of numbers in children aged 4-5 years at Kindergarten Amalia, Mandah District, at 62.90% and the N-Gain value was in the medium category.Keywords: Getting to know the concept of numbers, hop pingpong game, Early Childhood